The effect of interprofessional simulation practice on collaborative learning: A randomized controlled trial. - Costa Marion, Alexandra Daniela; Pereira, Leonardo Costa; Lucia Moura Pinho, Diana (Journal of Interprofessional Care)
This study examined the effect of simulation on readiness for collaborative practice and learning using a randomized-controlled trial design that used the same education protocol with interprofessional and uniprofessional groups. The sample consisted of 43 students from four different majors. The students were assessed with the Readiness for Interprofessional Learning Scale, and a care plan measurement instrument. The interprofessional group showed a small increase (0.1 ± 0.43; p =.02) in readiness for teamwork and collaboration; the uniprofessional group showed a smaller increase for teamwork and collaboration (0.04 ± 0.31; p =.04) and for patient-centred care (0.0 ± 0.35; p =.01). The enriching work of interprofessional learning was evident within the care plan activity, suggesting that interprofessional simulation is an effective learning method for interprofessional education.